(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: As most of breast cancer patients are treated with Tamoxifen, different effects of this drug in patients should be evaluated since no such study is carried out in Bangladesh till date. Objective: The purpose of the present study was to evaluate sonographic changes of female genital organs in breast cancer patients treated with Tamoxifen and to correlate these changes with duration of Tamoxifen treatment and gynecological symptoms. Methodology: This randomized double-blind clinical trial was carried out in Delta Medical College Hospital, Dhaka, Bangladesh from May 2017 to April 2018 for a period of one (1) year. The participants were breast cancer patients which were divided into three groups named as group I patients. The patients of these group were on Tamoxifen therapy. The patients of group II were without Tamoxifen therapy. The patients of group III had completed Tamoxifen therapy. All participants underwent ultrasonography. Results: Patients receiving Tamoxifen therapy had significantly more thickened endometrium compared to other groups (26.6% in group I, 5% in group II and3% in group III). Similarly, abnormal sonographic findings and mean uterine volume were higher in group I compared to other two groups. Endometrial thickness and uterine volume showed significant positive correlation with duration of Tamoxifen therapy (p <0.0001). The endometrial thickness and uterine volume greatly increased after two years of Tamoxifen therapy while it was reverse in group III. Gynecological symptoms had no significant relations with sonographic abnormalities and thickened endometrium. Conclusion: Tamoxifen therapy is associated with increased endometrial thickness, uterine volume and abnormal sonographic findings, compared to patients without Tamoxifen or completing Tamoxifen therapy. Journal of Current and Advance Medical Research 2020;7(1): 17-23